Illustrated identification guide of Malaysian Reduviidae latreille 1807 (Hemiptera: Heteroptera) - David A. D.,; Yaakop S.,; Idris Abd. Ghani, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2017)
An illustrated key for ten Reduviidae species belongs to four subfamilies were built using specimens collected in Malaysia.